IMPLIKASI HUKUM PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. MANDIRA MITRA COALINDO UNTUK KESEJAHTERAAN MASYARAKAT KECAMATAN MUARA BADAK - Sri YM, Feranda; Suryaningsi, Suryaningsi; Hardoko, Aloysius; Wingkolatin, Wingkolatin (Cahaya Ilmu Bangsa, 2025)
Abstract Legal Implications of Corporate Social Responsibility (CSR) Implementation of PT. Mandira Mitra Coalindo for Community Welfare in Muara Badak Regency aims to determine the regulations governing the implementation of Corporate Social Responsibility (CSR) of PT. Mandira Mitra Coalindo (MMC) for the welfare of the Muara Badak community, the CSR implementation program at PT. Mandira Mitra Coalindo for the welfare of the Muara Badak community and the benefits of CSR implementation at PT. Mandira Mitra Coalindo for the welfare of the Muara Badak community. The type of research used is qualitative. This research was conducted at the Mining Company PT. Mandira Mitra Coalindo East Kalimantan. The subjects of this study were the company's leaders accompanied by the head of CSR planning and implementation and the Muara Badak District community using observation, interview and documentation techniques. The results of this study indicate that the implementation of Corporate Social Responsibility (CSR) of PT. Mandira Mitra Coalindo in Mining activities has been in accordance with the rules and policies in the Indonesian mining business. The form of the Corporate Social Responsibility (CSR) program of PT. Mandira Mitra Coalindo is designed and implemented based on the needs of the community in the mining production area through deliberations or musrenbang carried out by the company together with government officials and the community. Deliberations with the government and the community resulted in CSR programs through several fields, namely education, health, economic independence, socio-culture and environmental management. The benefits felt by the Muara Badak Community are felt both economically, socially and culturally for the benefit and welfare of the community. Keywords: Law, Corporate Social Responsibility (CSR), PT. Mandira Mitra Coalindo, Muara Badak Community Welfare. Abstrak Implikasi Hukum Pelaksanaan Corporate Social Responsibility (CSR) PT. Mandira Mitra Coalindo untuk Kesejahteraan Masyarakat Kecamatan Muara Badak bertujuan untuk mengetahui hukum yang mengatur pelaksanaan Corporate Social Responsibility (CSR) PT. Mandira Mitra Coalindo (MMC) untuk kesejahteraan masyarakat Muara Badak, program dari pelaksanaan CSR di PT. Mandira Mitra Coalindo untuk kesejahteraan masyarakat muara badak dan m manfaat dari pelaksanaan CSR di PT. Mandira Mitra Coalindo untuk kesejahteraan masyarakat Muara Badak. Jenis penelitian yang digunakan kualitatif. Penelitian ini dilakukan di Perusahaan Tambang PT. Mandira Mitra Coalindo, Kalimantan Timur. Subjek penelitian ini ialah kepala pimpinan perusahaan dibersamai kepala perencanaan dan pelaksanaan CSR serta masyarakat kecamatan Muara Badak dengan menggunakan teknik observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa pelaksanaan Corporate Social Responsibility (CSR) PT. Mandira Mitra Coalindo dalam kegiatan Pertambangan sesuai dengan aturan dan kebijakan dalam usaha pertambangan Indonesia. Bentuk program Corporate Social Responsibility (CSR) PT. Mandira Mitra Coalindo dirancang dan dilaksanakan berdasarkan kebutuhan masyarakat daerah produksi tambang melalui musyawarah atau musrenbang yang dilaksanakan oleh perusahaan dibersamai oleh pejabat pemerintah dan masyarakat. Musyawarah dengan pemerintah dan masyarakat menghasilkan program CSR melalui beberapa bidang yaitu bidang pendidikan, kesehatan, kemandirian ekonomi, sosial budaya dan pengelolaan lingkungan. Manfaat yang dirasakan Masyarakat Muara Badak dirasakan baik secara ekonomi, sosial dan budaya untuk kepentingan dan kemakmuran masyarakat. Kata kunci: Hukum, Corporate Social Responsibility (CSR), PT. Mandira Mitra Coalindo, Kesejahteraan Masyarakat Muara Badak.